Combining Electrolysis and Electroporation for Tissue Ablation. (August 2015) - Phillips, Mary; Rubinsky, Liel; Meir, Arie; Raju, Narayan; Rubinsky, Boris
Electrolytic ablation is a method that operates by delivering low magnitude direct current to the target region over long periods of time, generating electrolytic products that destroy cells. This study was designed to explore the hypothesis stating that electrolytic ablation can be made more effective when the electrolysis-producing electric charges are delivered using electric pulses with field strength typical in reversible electroporation protocols. (For brevity we will refer to tissue ablation protocols that combine electroporation and electrolysis as E 2 .) The mechanistic explanation of this hypothesis is related to the idea that products of electrolysis generated by E 2 protocols can gain access to the interior of the cell through the electroporation permeabilized cell membrane and therefore cause more effective cell death than from the exterior of an intact cell. The goal of this study is to provide a first-order examination of this hypothesis by comparing the charge dosage required to cause a comparable level of damage to a rat liver, in vivo, when using either conventional electrolysis or E 2 approaches. Our results show that E 2 protocols produce tissue damage that is consistent with electrolytic ablation. Furthermore, E 2 protocols cause damage comparable to that produced by conventional electrolytic protocols while delivering orders of magnitude less charge to the target tissue over much shorter periods of time.